Metode Al-Bidayah Dalam Meningkatkan Kemampuan Reseptif Bahasa Arab: Qiraah - Frisna Septian Renaldi; Luk-Luk Nur Mufidah; Anin Nurhayati (LP3M IAI Al Urwatul Wutsqo Jombang, 2023)
Methods are regular means used to carry out a job. The method has a purpose so that the material to be delivered can be received by students well. The choice of learning methods must be adjusted to the needs of students, because improper learning methods will cause the learning process to take place less effectively and learning objectives cannot be carried out optimally. The al-bidayah method is one of the methods in Arabic language learning that is considered effective for learning students' maharah qiraah. Using a qualitative library research approach, this article reviews the complex al-bidayah method and its role in increasing reseptive. Abillities in the form of maharah qiraah. Reseachers obtained data by reading, writing and analyzing the conntents pf the manual for the al-bidayah method and using it as a primary research data source. The results showed that al-bidayah method is an applicable method used for reseptive learning of arabic. This is because al-bidayah method has a systematic arragement of chapters and sub-chapters. The role of the al-bidayah method in improving students’ reseptive abilities is in the aspects of nahwu and sharf.